Systematic revision of the tribe Ennadini (Lepidoptera: Geometridae) in southern South America, with descriptions of new genera and species - Ramos-González, Mario I.; Zamora-Manzur, Carlos; Garrido, Carolina Rose; Parra, Luis E. (Zootaxa, 2026)
An integrative taxonomic revision of the tribe Ennadini is presented for southern South America, based on adult morphological characters and a time-calibrated molecular phylogeny inferred from 11 genetic regions. The tribe is recovered as monophyletic, with an estimated crown age of 29.8 million years (Oligocene), according to a relaxed lognormal molecular clock model. The genera Ennada Blanchard and Spargania Guenée are redefined, and Praeapodroma Heimlich is transferred to Ennadini. Three new genera are described: Antuluciella gen. nov., Incantia gen. nov., and Kuyenusia gen. nov. Five new combinations are proposed: Antuluciella vittata (Philippi) comb. nov., Incantia edmondsii (Butler) comb. nov., Kuyenusia ceres (Butler) comb. nov., Praeapodroma macerata (Felder & Rogenhofer) comb. nov., and Praeapodroma scarata (Felder & Rogenhofer) comb. nov. Two new synonymies are established: Fidonia incandescens Thierry-Mieg = Incantia edmondsii (Butler), syn. nov.; and Heterusia mesenata Felder & Rogenhofer = Antuluciella vittata (Philippi), syn. nov. The reinstatement of Spargania pastoralis (Butler) comb. rev. is also proposed, and Kuyenusia tenten Ramos-González & Parra sp. nov. is described. Diagnostic characters, redescriptions, and distributional data are provided for all treated species. Lectotypes are designated where necessary to stabilize nomenclature. This revision provides a robust and updated systematic and evolutionary framework for Ennadini moths in the temperate regions of South America.